Evaluasi Pemberian Bahan Allograft dan Alloplast pada Penderita Periodontitis Agresif Menyeluruh dengan Genotipe Positif Alel 2 (+3954) Interleukin-1 Beta - Andrena Andrena; Yuniarti Soeroso; Endang W. Bachtiar (Faculty of Dentistry, Universitas Indonesia, 2013)
Generalized aggressive periodontitis is a disease or a disorder of periodontium that occurs in people below 30 years old. These patients usually have several immune response disorders, such as defects in chemotaxis, phagocytic of neturophils and monocytes, and genetic defect. Clinically, there are generalized losses of tissue attachment with extensive, rapid and progressive alveolar bone resorption. In order to repair bone destruction, treatment that produce bone regeneration is needed, i.e. full thickness flap with bone grafting. In these cases, allograft and alloplast bone grafts were used. Allograft is derived from subjects within the same species but different individuals, whereas alloplast is foreign body embedded into the tissue (e.g. hydroxylapatite). In this report, pocket depth, papillae bleeding index (PBI), and clinical attachment were evaluated. Six month after surgery and bone grafting, there were + 4 mm decrease of pocket depths, bleeding on probing index and 3-4 mm increase of clinical attachment. Unstimulated wholes saliva were also collected for DNA isolation. The IL-1beta(+3954) genotypes were performed by Polymerase chain reaction, digested with TagI restriction enzyme and separated by gel electrophoresis. Results showed both patients bearing allele 2 homozygous of IL-1B+3954 genotype. This genotype has been identified as the one of immunogenetic factor that could affect the severity of periodontal disease. Successful treatment depends on the adequacy of oral hygiene. Patients were advised to maintain optimal oral hygiene and to do periodic check every 2-3 months. DOI: 10.14693/jdi.v15i2.70